ESTIMATION OF GENETIC PARAMETERS FOR SEVERALQUALITITIV CHARACTERS IN HYBRIDS OF TOBACCO ATOPEN FIELD - Al-Shamma, Laith; Baktash, Fadel (Iraqi Journal of Science, 2024)
Full diallel crosses conducted to develop tobacco (Nicotiana tabacum L) hybridsusing three cultivars; Corjo (A), Sumer48 (B) and Croillo (C), during 2004. Hybridtrail carried out at the open field using Randomized Complete Block Desighn with 3parents, 6 hybrids and 2 control, Habana and CV. 48.Significant differences werefound among studied characters except the pH of the tobacco. The hybrid (AxB) hadhigher percentage of nicotine (2.62%), ash (9.60) and sugar percentage (8.01), whilethe hybrids (AxC) and (BxC) revealed highest burning speed (0.056 & 0.055).Several crosses revealed positive and negative heterosis in the studied traits. Geneticanalysis showed that the studied characters were under non additive gene action. Itwas concluded that the hybridization is the best method to improve those traits.